Mercury in the Black Sea: New Insights From Measurements and Numerical Modeling. Issue 4 (13th April 2018) - Rosati, G.; Heimbürger, L. E.; Melaku Canu, D.; Lagane, C.; Laffont, L.; Rijkenberg, M. J. A.; Gerringa, L. J. A.; Solidoro, C.; Gencarelli, C. N.; Hedgecock, I. M.; De Baar, H. J. W.; Sonke, J. E.
Abstract: Redox conditions and organic matter control marine methylmercury (MeHg) production. The Black Sea is the world's largest and deepest anoxic basin and is thus ideal to study Hg species along the extended redox gradient. Here we present new dissolved Hg and MeHg data from the 2013 GEOTRACES MEDBlack cruise (GN04_leg2) that we integrated into a numerical 1‐D model, to track the fate and dynamics of Hg and MeHg. Contrary to a previous study, our new data show highest MeHg concentrations in the permanently anoxic waters. Observed MeHg/Hg percentage (range 9–57%) in the anoxic waters is comparable to other subsurface maxima in oxic open‐ocean waters. With the modeling we tested for various Hg methylation and demethylation scenarios along the redox gradient. The results show that Hg methylation must occur in the anoxic waters. The model was then used to simulate the time evolution (1850–2050) of Hg species in the Black Sea. Our findings quantify (1) inputs and outputs of HgT (~31 and ~28 kmol yr −1 ) and MeHgT (~5 and ~4 kmol yr −1 ) to the basin, (2) the extent of net demethylation occurring in oxic (~1 kmol yr −1 ) and suboxic water (~6 kmol yr −1 ), (3) and the net Hg methylation in the anoxic waters of the Black Sea (~11 kmol yr −1 ). The model was also used to estimate the amount of anthropogenic Hg (85–93%) in the Black Sea. Key Points: The 2013 GEOTRACES MEDBlack cruise data show the highest MeHg percentages (up to 57%) in permanently anoxic waters, comparable to oxic open‐ocean subsurface maxima We implemented a 1‐D numerical model for Hg dynamics and assessed the occurrence of Hg methylation and demethylation along the stretched redox gradient The Hg species model and budget suggest that input from rivers, the Mediterranean Sea, and sediment are negligible and that MeHg is produced in situ in anoxic waters